Demetrius sacker of cities - Romm, James S. (Yale University Press, 2022)
A portrait of one of the ancient world's first political celebrities, who veered from failure to success and back again
Keywords: Demetrius -- I, -- Poliorcetes, King of Macedonia, -- 336 B.C.-283 B.C.; Macedonia -- Kings and rulers -- Biography.; BIOGRAPHY & AUTOBIOGRAPHY / Royalty; Kings and rulers; Europe -- Macedonia; Biographies